The Influence Of Transformational Leadership Style, Work Discipline, And Work Motivation On The Performance Of Perum Bulog Indramayu Employees - Peni Apitasari; Derih Derih; Anesta Rosa Indah Fatanshe; Siti Maryam (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Increasingly fierce competition causes companies to be able to increase competitiveness in order to maintain the company's survival. With these demands, the production process in the company environment generally requires maximum results, and related to this, the company must be able to maximize employee performance. The purpose of this study is to examine the influence of the variables of transformational leadership style, work discipline, and work motivation on employee performance both partially and simultaneously. The method that will be used in this research is to use a descriptive quantitative method using instrumental tests in the form of validity tests, reliability tests, and data analysis using regression tests. The results of this study show that the transformational leadership style has a positive effect on employee performance partially, work discipline has a positive effect on employee performance partially, and work motivation is influential